Investigation of the Morphometric Diversity of Ali Kazemi Rice in Iran - Seyedeh Mahsa Safiedin Ardebili; Reza Azizinezhad; Sara Saadatmand; Rahim Ahmadvand; Iraj Mehregan (Journal of Genetic Resources)
In this study, the experiment was carried out in a completely randomized design to discover the diversity among 300 Ali Kazemi rice populations from three provinces (ten populations) in the north of Iran using SPSS, Past, Graph Pad, and Excel software. The studies were conducted based on 30 morphological traits. Quantitative traits, like panicle traits, grain length, 100-grain weight, and number of spikelets, demonstrated high variation between populations. Cluster and ordination analyses were performed on morphological characters. The cluster analysis made it possible to divide the Ali Kazemi rice into three sub-clusters of different geographical regions, showing this local variety’s adaptability to the environment. Of the three populations, Guilan appeared to be more variable than the Qazvin and Zanjan, as variability was observed among populations for some characters, such as awn length, number of spikelets, blade length, and panicle traits between populations. GLN01 had the highest average plant height (1185.60 mm). The populations of Guilan also had the longest leaf blade and stem length. The highest value for grain size was also recorded from the Guilan populations. For the ten Ali Kazemi rice populations, the ordinal analysis revealed the traits that cause the greatest variation between populations. Highly significant correlations were found between awn length and traits such as grain length (r= 0.395), panicle length (r= 0.477), panicle weight (r= 0.349), and 100-grain weight (r= 0.440). The highest correlation was between the number of spikelets and some traits, such as plant height, leaf length, culm outer diameter, number of tillers, and panicle traits, indicating that a selection advantage for panicle traits occurs mainly for quantitative traits. Overall, the data collected in the present study could have valuable implications for improving Ali Kazemi rice cultivars in farmers' fields.